1953
DOI: 10.1071/bt9530071
|View full text |Cite
|
Sign up to set email alerts
|

The tertiary occurrence and distribtion of Podocarpus (section Dacrycarpus) in Australia and Tasmania

Abstract: Proof of the occurrence of the section Dacrycarpus of the genus Podocarpus in Australia and Tasmania is presented.Foliage shoots with structure preserved from Yallourn, Victoria, have been designated hypotypes of Podocarpus praecupressinus Ett. Pollen grains of the Dacrycarpus type have been identified in a number of widely separated Tertiary deposits. The sporotype Dacycarpites has been instituted for them and one sporomorph Dacrycarpites australienis described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1955
1955
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…Architectural features: vegetative shoots bearing small, simple, scale-like, spirally inserted leaves, defoliation units unbranched axes. Leaves decurrent and appressed, but on some axes regularly spaced, slightly spreading (similar to those illustrated by Cookson and Pike, 1953. fig.…”
Section: (C) (D) (T) (G) 5)supporting
confidence: 61%
See 1 more Smart Citation
“…Architectural features: vegetative shoots bearing small, simple, scale-like, spirally inserted leaves, defoliation units unbranched axes. Leaves decurrent and appressed, but on some axes regularly spaced, slightly spreading (similar to those illustrated by Cookson and Pike, 1953. fig.…”
Section: (C) (D) (T) (G) 5)supporting
confidence: 61%
“…Rich) de Laubenf. (Cookson and Pike, 1953;Wells and Hill, 1989a, b), and I propose that they are conspecific. The cutin envelope seen over the guard cells of extant D.…”
Section: Dacrycarpusmentioning
confidence: 93%
“…Cookson and Pike (1953~) regarded the coal containing Dacrycarpus praecupressinus to be widespread in the Yallourn coal seam, and Blackburn (unpublished data, 1985) reported that the species was widespread in both the Yallourn and Morwell coal seams. This coal ranges in age from Late Oligocene to Miocene and possibly into the Pliocene (Stover and Partridge 1973).…”
Section: Methodsmentioning
confidence: 96%
“…Cookson and Pike (1953~) reported D. praecupressinus in a sandy layer on top of the coal at the Lucifer Mine, Bacchus Marsh, to which they assigned a probable Oligocene age (Cookson and Pike 1954).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation